(untitled) (Revista Española de Fisiología, 1991)
Enzymatically isolated dog lung and gut mast cells were stimulated with compound 48/80, ionophore A23187, concanavalin A and FNa-Ca. Cell response elicited by A23187, concanavalin A or 48/80 is almost completely inhibited by isoproterenol. Concanavalin A induced histamine release on gut mast cells is high, indicating an elevated degree of sensitization of these cells. Results point to the existence of beta adrenergic inhibitory activity on dog lung and gut mast cells.